Monocytic Myeloid-Derived Suppressor Cells in Chronic Infections - Dorhoi, Anca; Du Plessis, Nelita (Frontiers in Immunology, 2018)
Heterogeneous populations of myeloid regulatory cells (MRC), including monocytes, macrophages, dendritic cells and neutrophils, are found in cancer and infectious diseases. The inflammatory environment in solid tumors as well as infectious foci with persistent pathogens promotes the development and recruitment of MRC. These cells help to resolve inflammation and establish host immune homeostasis by restricting T lymphocyte function, inducing regulatory T-cells and releasing immune suppressive cytokines and enzyme products. Monocytic MRC, also termed monocytic myeloid-derived suppressor cells (M-MDSC), are bona fide phagocytes, capable of pathogen internalization and persistence, while exerting localized suppressive activity. Here we summarize molecular pathways controlling M-MDSC genesis and functions in microbial-induced non-resolved inflammation and immunopathology. We focus on the roles of M-MDSC in infections, including opportunistic extracellular bacteria and fungi as well as persistent intracellular pathogens, such as mycobacteria and certain viruses. Better understanding of M-MDSC biology in chronic infections and their role in antimicrobial immunity, will advance development of novel, more effective and broad-range anti-infective therapies.